Stream and shallow groundwater nutrient concentrations in an Ozark forested riparian zone of the central USA - Chinnasamy, Pennan; Hubbart, J.A. (Springer, 2015)
Characterizing spatiotemporal variations in surface water (SW)–shallow groundwater (GW) nutrient concentrations is important to predict stream ecosystem responses to disturbance. Unfortunately, there is a lack of such information from mixed-deciduous semi-karst hydro-geological regions. Nitrate (NO3 -), total phosphorous (P), potassium (K) and ammonium (NH4 +) concentrations were monitored in a case study between an Ozark stream and riparian hardwood forest GW over the 2011 water year in the central USA. Average SW NO3 -, P, K and NH4 + concentrations were 0.53, 0.13, 3.29 and 0.06 mg L-1, respectively. Nine meters from the streambank, average GW NO3 -concentration was 0.01 mg L-1, while P, K and NH4 + concentrations were 0.03, 1.7 and 0.04 mg L-1, respectively. Hyperbolic dilution model results indicated that NO3 - and K exhibited dilution behavior, while NH4 + had a concentration effect and P was hydrologically constant. Observed seasonal NO3 - concentration patterns of winter maxima and summer minima in SW (1.164 and 0.133 mg L-1) and GW (0.019 and 0.011 mg L-1) were supported by previous studies yet exhibited distinct semi-karst characteristics. Results indicate that in addition to relatively low residence time, lower nutrient concentrations in GW (relative to SW) may suggest that shallow GW flow processes are important for vegetation removal and retention of nutrients from streams in semi-karst shallow groundwater systems of the central USA.